Arming America at war : a model for rapid defense aquisition in time of war - Blakeman, Seth T.; Gibb, Anthony R.; Jeyasinam, Jetanthan; Jones, Lawrence R. (Emerald Publishing Limited : Information Age Publishing, 2010)
This book follows the evolution of a model for quick and efficient national defense war fighting asset acquisition during time of war. It documents the case of a critically important war fighting acquisition program from initial needs identification and program start in 2006 through production and fielding in the period 2007-2010. The analysis focuses on the entire process of acquisition and contracting from concept development through getting the weapons system into action in Iraq, Afghanistan and elsewhere. The Mine Resistant Ambush Protected vehicles program (MRAP) is a rapid acquisition program procured within the context of the US Department of Defense's Acquisition Management and Joint Capabilities Integration and Development System (JCIDS) framework.The analysis in this book answers the following question: What are the key factors that explain the success of the MRAP program, with success defined as meeting program objectives and warfighter needs? In addition, this book addresses the critical trade-offs made within the MRAP program to develop it rapidly, and some of the potential long-term impacts of these decisions, both positive and negative, for rapid defense asset acquisition in time of war.
Keywords: Vehicles, Military -- United States.; Armored vehicles, Military -- United States.; United States. -- Department of Defense -- Procurement.; United States -- Armed Forces -- Equipment.; Iraq War, 2003-2011 -- Equipment and supplies.; Business & Economics -- Management.; Management of assets: real estate, property and plant.; Management and management techniques.; elektronické knihy; electronic books